2017
DOI: 10.1016/j.bonr.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Systemic analysis of osteoblast-specific DNA methylation marks reveals novel epigenetic basis of osteoblast differentiation

Abstract: DNA methylation is an important epigenetic modification that contributes to the lineage commitment and specific functions of different cell types. In this study, we compared ENCODE-generated genome-wide DNA methylation profiles of human osteoblast with 21 other types of human cells in order to identify osteoblast-specific methylation events. For most of the cell strains, data from two isogenic replicates were included, resulting in a total of 51 DNA methylation datasets. We identified 852 significant osteoblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 70 publications
1
11
0
Order By: Relevance
“…In addition to Rbpjκ, we recently identified hypomethylation in Cxcl12 gene in Dnmt3b LOF chondrocytes (20), suggesting Dnmt3b LOF could directly modify DNA methylation pattern in chondrocyte maturation-related genes. Findings from other groups also demonstrated that chondrogenic-and osteogenic-related genes could be regulated via alteration of DNA methylation in promoters (41)(42)(43). We thus speculate Dnmt3b LOF leads to progenitor differentiation defect through a combination of an altered Notch pathway and the alteration of DNA methylation in chondrogenic-and osteogenic-specific genes.…”
Section: Discussionsupporting
confidence: 62%
“…In addition to Rbpjκ, we recently identified hypomethylation in Cxcl12 gene in Dnmt3b LOF chondrocytes (20), suggesting Dnmt3b LOF could directly modify DNA methylation pattern in chondrocyte maturation-related genes. Findings from other groups also demonstrated that chondrogenic-and osteogenic-related genes could be regulated via alteration of DNA methylation in promoters (41)(42)(43). We thus speculate Dnmt3b LOF leads to progenitor differentiation defect through a combination of an altered Notch pathway and the alteration of DNA methylation in chondrogenic-and osteogenic-specific genes.…”
Section: Discussionsupporting
confidence: 62%
“…The roles of this DNA methylation remain unclear as well as how these regions are established, maintained, and function. Nevertheless, increasingly more studies are identifying the methylation of these regions as regulators of gene expression 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Canonical CpG islands have 300–3000 base pairs and have been found in approximately 70% of promoters located near the transcription start site (TSS) of a human gene such as housekeeping gene, tissue-specific gene, and regulator gene [ 21 ]. The methylation in CpG islands, as well as in CpG island-surrounding regions which contain shores and shelves, had strong correlation with the transcription initiation and chromosome configuration [ 22 ] and affected human health [ 23 , 24 ]. Here, we defined the methylated differences across SLE, RA, and pSS with two principles: (i) there are statistical significances in the analyses of DMVs; (ii) in all three disorders, at least one disorder has a differential methylation status that is completely opposite to the other two, namely, if there is a significant hypermethylated site in SLE, then this site must be significantly decreased in the other two diseases.…”
Section: Resultsmentioning
confidence: 99%